(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2026)
In the field of medicine, pancreatic diseases are widespread in the practice of gastroenterology, and modern instrumental examination methods are of great importance for the early detection of this disease and differential diagnosis with other diseases. Also, today ultrasound examination (USG) is a non-invasive, safe, and widely used diagnostic method. Therefore, in scientific research, the diagnostic significance of ultrasound in the early detection of pancreatic diseases is analyzed.